2011
DOI: 10.1186/1471-2458-11-655
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol: a pragmatic randomised controlled trial of a 12-week physical activity and nutritional education program for overweight Aboriginal and Torres Strait Islander women

Abstract: BackgroundAboriginal and Torres Strait Islander women have a higher prevalence and incidence of obesity and type 2 diabetes than non-Indigenous Australian women. Physical inactivity is a key modifiable risk factor for obesity and evidence shows that even modest reductions in waist circumference (WC) have significant health benefits. Trialing physical activity programs in difficult-to-reach high risk groups, especially urban Indigenous Australians poses distinct implementation challenges.Methods/DesignThe trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 24 publications
0
53
0
Order By: Relevance
“…While the 10 studies all aimed to enhance various dimensions of PYD, interventions primarily did so via a main goal of reducing risky behaviors (n = 6) [17,19,22,23,25,26], preventing the onset of chronic diseases (n = 3) [11,20,21], or promoting cultural connectedness (n = 1) [24]. Most of the studies were quasi-experimental (n = 8) [11, 17, 19, 21-23, 25, 26], but randomized controlled trial designs (n = 2) [20,24] were also utilized.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…While the 10 studies all aimed to enhance various dimensions of PYD, interventions primarily did so via a main goal of reducing risky behaviors (n = 6) [17,19,22,23,25,26], preventing the onset of chronic diseases (n = 3) [11,20,21], or promoting cultural connectedness (n = 1) [24]. Most of the studies were quasi-experimental (n = 8) [11, 17, 19, 21-23, 25, 26], but randomized controlled trial designs (n = 2) [20,24] were also utilized.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies were quasi-experimental (n = 8) [11, 17, 19, 21-23, 25, 26], but randomized controlled trial designs (n = 2) [20,24] were also utilized. Studies were conducted in the USA (n = 6) [11,17,19,22,23,26], Canada (n = 2) [21,25], and Australia (n = 2) [20,24]. Studies reported an average of 9.70 (±3.24) out of 21 RE-AIM items, ranging from 5 to 14 reported items ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations